Reconfigurable Metamaterial Comprised of Dielectric Resonators and Plasma - Fantini, Lisa. (Tufts University. Tisch Library., 2019)
Metamaterials have applications in fields spanning biology to electrical engineering. Advancing metamaterial technology can improve their performance in current applications and also lead to more applications. I continued to investigate a metamaterial made out of dielectric resonators and plasma by scaling it down, making it into a 2-D structure, and comparing it to theory. I used Raizer theory, simulations on ANSYS HFSS, and experimental results to determine the best conditions for plasma formation. Dielectric resonators (calcium titanate cylinders with ~5.7 mm diameters and ~1.9 mm heights) separated by 0.25 mm and with their flat sides facing each other, formed plasma in their HEM111 resonance mode, at ~4 Torr and in the range of 6-7 GHz. Turning the plasma on and off changed the transmission properties of the metamaterial, leading to tunability. Dielectric resonators can have a negative permeability, and plasma can have a negative permittivity, therefore this metamaterial could potentially have a negative index of refraction (NIR), which could lead to novel applications such as "perfect" lenses.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Electrical Engineering.; Advisor: Jeffrey Hopwood.; Committee: Timothy Atherton, and Thomas Vandervelde.; Keywords: Electrical engineering, Materials Science, and Physics.